Analisis Keunggulan Bersaing Terhadap Keberhasilan Usaha - Zikriatul Ulya Zikri; Noer Zainora (Journal Research of Economic and Bussiness, 2023)
Success in entrepreneurship has a goal to build competitive advantage and must have a clear direction and do not hesitate to start a business from a new direction to be able to initiate major changes, in order to obtain high income and be able to survive in the long term. The purpose of this study was to determine the effect of entrepreneurial motivation and competitive advantage on business success at fashion stores in the Blok B market, Langsa City. This study uses primary data sourced from research questionnaires with a sample of 50 respondents. The quantitative descriptive data analysis method uses multiple linear regression equations, t test, F test and the coefficient of determination (R2) test. The results showed that entrepreneurial motivation and competitive advantage have a positive effect on business success in fashion stores in the Blok B market, Langsa City, which is known from the multiple linear regression equation Y = 13.556 + 0.543X1 + 0.287X2. The results of the t test show that entrepreneurial motivation has a significant effect on business success. Competitive advantage has a significant effect on business success. Then the results of the F test, simultaneously entrepreneurial motivation and competitive advantage have a significant effect on business success. The results of the coefficient of determination (R2) showed that 69.3% entrepreneurial motivation and competitive advantage were able to explain the dependent variable of business success.